Performance Analysis of Efficient Energy Management in Routing Protocol for Mobile Wireless Sensor Network - B, Anil Kumar; Rao, K Ramkee (IJRDO -Journal of Computer Science Engineering, 2015)
Wireless Sensor Networks (WSN) are promising andvery appealing technology applied to different applications.Nodes(sensors) of a wireless sensor networks (WSNs) arepowered by exhaustible batteries with limited life span andgenerally they are non-rechargeable. As the deployment of theseWSNs occurs in harsh areas generally inaccessible and sometimeshostile, the replacement of depleted batteries is not feasible, sonodes must therefore ensure their mission with their uniqueinitial strict energy budget. This constraint makes the energyresource the most decisive and of critical importance in theWSNs. The routing protocols have to pay much attention in thiscontext of energy conservation. Cluster based routing protocolshave significant impact on the energy dissipation and life time ofwireless sensor networks (WSN). In this paper the proposedtechnique PEGASIS-MAEM(PEGASIS- Mobile average energybased) protocol for Multi hop network will be achieved bycombining LEACH-MAE[1] based protocol with PEGASISMH[2]]protocol. This novel technique overcomes the pitfalls inpresent protocols and gives better mobile average energy basedCluster Head selection. All the simulations are carried out in NS2simulator. Simulation results shows that our proposed protocolPEGASIS-MAEM outperforms compared to the other protocols.